Revealing the relationship of human convergence–divergence patterns and land use: A case study on Shenzhen City, China. (December 2019) - Yang, Xiping; Fang, Zhixiang; Yin, Ling; Li, Junyi; Lu, Shiwei; Zhao, Zhiyuan
Abstract: Understanding the relationship between human mobility and land use has been a longstanding topic in multiple disciplines, including transport geography and urban planning. Recently, urban collective mobility patterns have become a hot research direction and has been explored at an unprecedented space–time scale due to the emerging big human tracking datasets (e.g., mobile phone data). However, only a few studies have comprehensively quantified the effects of land use on human mobility patterns while considering the influence of the scale of spatial analysis units. This study attempts to reinforce this knowledge by investigating urban human convergence–divergence patterns and their relationship with land use distribution characteristics at three popular types of spatial analysis units of human mobility studies (voronoi polygons, grid cells, and traffic analysis zones) using mobile phone data. A case study on Shenzhen, China is implemented, and results indicate that eight distinct convergence–divergence patterns could be extracted to describe urban collective mobility patterns despite the use of different types of spatial analysis unit. Moreover, the scale of spatial analysis units exerts a few effects on the quantification of the influence of land use distribution on human convergence–divergence patterns, but some common characteristics could be summarized from these discrepant results. The findings can help policy makers understand urban human mobility and can serve as a guide for urban management and planning. Highlights: Human convergence–divergence patterns and their relationship with land use distribution characteristics are investigated. Three popular types of spatial analysis units are used to check the effect of MAUP. Eight distinct convergence–divergence processes are extracted to describe urban human mobility patterns. Some common land use characteristics are summarized from three types of spatial analysis units.